Coconut residue flour in bread (Pan de sal) - Pua, Marigold Santos
The study was divided into two phases. In the first phase, the effects of substituting parts of all purpose flour with coconut residue flour was determined through objective and subjective tests. Under the conditions of the experiment, results showed that there was an inverse relationship between substitution and bread volume. As percent substitution increases, a more compact bread is obtained. Average volume measurements were 360.1 ml, 266.1 ml and 255.3 ml for 3%, 5% and 7% levels respectively. From the subjective test results, as percent distribution increases, panelists have detected a coarser crumb. Coarseness range was 1 ≤ x < 5 and fineness range was 5 < x < 9. Average or mean scores were 6.72, 4.84, and 4.84 for 3%, 5% and 7% respectively. Based from the overall acceptability, the panelists gave mean scores of 6.24, 5.28 and 4.40 for 3%, 5% and 7% respectively, hence a reference for the 3% substitution. This recipe was in turn replicated in the second phase and was evaluated against a control bread. Same tests were performed during the evaluation. Volume difference was not apparent in the ink imprint and comparison by photography test but became evident when volume measurement by seed displacement method and height measurement tests were done. The control had greater volume compared to the 3% CRF-substituted bread. Average volumes were 364.8 ml and 333.8 ml respectively. No significant difference was established in terms of color, contour, internal grain, coconut odor, coconut flavor and mastication. From the overall acceptability, control was preferred over 3%. The scores were 6.88% for control and 4.68% for 3%. The components of the 3% CRF-substituted bread were: 27.6% for moisture, 8.70%for crude fat, 9.40% for crude protein, 0.74% for crude fiber and 1.40% for ash.